Determinant Yield To Maturity of Banking Sector Bonds Listed On The Indonesia Stock Exchange For The Period 2015-2020 - Elfira Riani Syamsu; Endri Endri (Ridwan Institute, 2022)
This study identifies the factors that affect the Yield to Maturity of Banking Sector Bonds Listed on the Indonesia Stock Exchange for the 2015-2020 Period. The population in this study are banking sector companies listed on the Indonesia Stock Exchange for the 2015-2020 period. The sampling technique was purposive sampling which obtained as many as 11 companies consisting of 22 corporate bonds which were used as research objects. The dependent variable in this study is Yield to Maturity (YTM) while the dependent variable is Interest Rate (IRATE), Exchange Rate (KURS), Leverage (DER), Liquidity (CR) and Firm Size (SIZE). The research analysis method used is descriptive statistics and panel data regression Random Effect Model (REM) which is processed using E-VIEWS 12. The purpose of this study is to analyze the influencing factors and their implications for the yield to maturity of corporate bonds, based on their respective relationships. variable or simultaneously. The results showed that partially the Interest Rate variable had a significant negative effect on Yield to Maturity and Exchange Rate had a significant positive effect on Yield to Maturity, while the Leverage, Liquidity and Firm Size variables had no effect on Yield to Maturity